ANALISIS KEBIJAKAN PERSEDIAAN BAHAN KEBERSIHAN GEDUNG TELKOM NON-BUILDING MANAGEMENT (BM) AREA KOTA BANDUNG MENGGUNAKAN EOQ - Carvin Prawira Ramadhan (LPPM STIE Muhammadiah Bandung, 2025)
Managing cleaning material inventory is crucial to ensure adequate stock availability without incurring excessive storage and ordering costs. This study aims to examine the use of the Economic Order Quantity (EOQ) method in managing cleaning material inventory in the Telkom Non-Building Management (BM) Building in the Bandung. The EOQ method is used to determine the optimal quantity to minimize total inventory costs (including ordering and storage costs). The analysis results indicate that the application of EOQ can optimize the cleaning agents’procurement with better cost efficiency than conventional ordering methods. Keywords: Economic Order Quantity (EOQ), inventory, cleaning materials, inventory costs, operational management.